Effects of maize/peanut intercropping system on nodulation of peanut in northwest Liaoning. Issue 1 (February 2021) - Feng, Chen; Ma, Xiaohui; Feng, Liangshan; Zheng, Jiaming; Bai, Wei; Yang, Ning; Xiang, Wuyan; Cui, Xue; Sun, Zhanxiang
Abstract: The maize/peanut intercropping system was considered as a technique, which can both reduce drought risk of sole maize and wind erosion of sole peanut in northwest Liaoning. To clarify the nodulation characteristic of peanut in maize/peanut intercropping system of semi-arid area in northwest Liaoning, a field experiment was conducted at National Agricultural Experimental Station for Agricultural Environment, in northwest Liaoning, China. Including three cropping system (M2P4, M4P4 and Sole peanut) and three densities of maize (2, 3, 4 plants m −2 for M2P4, 3, 4.5, 6 plants m −2 for M4P4) based on the configuration. The results showed that Intercropped with maize significantly promote the nodulation of peanut. The nodule number and nodule size of peanut in M4P4 was significantly more than that of intercrops M2P4 and monoculture. Increasing the proportion of maize in row promotes the nodulation of peanut in maize/peanut intercropping system. The middle density of maize (3 plants m −2 ) is the best density for peanut nodulation in M2P4 intercropping system. 3 plants m-1 density of maize is better for nodulation of peanut in earlier stage of peanut growth in M4P4 system, while the high maize density (6 plants m −2 ) is more suitable for peanut nodulation in middle and later periods.